An all-in-one tool for multipurpose ecological risk assessment and management (MeRAM) of chemical substances in aquatic environment. (April 2021) - Lin, Bin-Le; Meng, Yaobin; Kamo, Masashi; Naito, Wataru
Abstract: A quality-assured ecological risk assessment (ERA) requires enormous resources (time and labor) in collection/assessment of hazard data, as well as considerable expertise to interpret the risk. The ERA of chemicals is thereby considered difficult or impossible for those with little assessment experience and cumbersome or complicated for practitioners. To meet the concerns regarding ERA and accelerate the risk assessment and management of chemicals, we developed an all-in-one free tool for multi-purpose ecological risk assessment management (MeRAM) of chemical substances in aquatic environment called the AIST-MeRAM Ver. 2.0.0 (Copyright No: H28PRO-2007). It allows users from beginners to experts to conduct ERA without any preparation because all the necessary ecotoxicity test data and methodologies are available in the system. Approximately 270, 000 ecotoxicity test data points for 3900 chemical substances together with the scientific methodologies from traditional simple hazard quotient (HQ) to more ecologically relevant complicated assessments such as species sensitivity distribution (SSD) and population-level assessment are embedded in the AIST-MeRAM. In addition, users can easily understand the Japanese regulatory RA and management of chemical substances due to a special function based on the Japanese Chemical Substance Control Law (CSCL). Here, we demonstrate a tiered ERA using the embedded sample data to evaluate and ensure the functions of AIST-MERAM. We show that the AIST-MeRAM can provide a comprehensive and accurate ERA, suggesting that it is a powerful IT solution for cumbersome ERA. Graphical abstract: Image 1 Highlights: A free IT solution for ecological risk assessment (ERA) called AIST-MeRAM was developed. Database (e.g., ecotoxicity data) and available ERA methods were embedded for saving required labor and time. Perform the ERA by an intuitive mouse click right after installation on your Windows PC. AIST-MeRAM affords point/probabilistic risk estimations and auto-setting of uncertainty factors. As a legal template referring to the scheme of Chemical Substances Control Law for developing countries.